The Incang-Incang Tradition of the Pedamaran Village Community, Ogan Komering Ilir 2001-2023 - Suci Meilany; Mareta, Yoan; Purnomo, Budi (Journal of Indonesian History, 2024)
This study discusses the Incang-incang Tradition of the Pedamaran Village Community, Ogan Komering Ilir 2001-2023. The incang-incang tradition is a local product of the South Sumatra region that has not been widely introduced to the Indonesian people. Incang-incang is a poem in the form of pantun, expressed in a regular tone and using the Panesak language as the everyday language of the Pedamaran community. This study aims to describe the Incang-incang Tradition of the Pedamaran Village Community, Ogan Komering Ilir 2001-2023. The type of research used is historical research. The method of collecting research data is obtained through observation, interviews and document searches or literature studies. In the Incang-incang tradition, it is used as a form of entertainment for the Pedamaran community which can be done with or without reciprocation, and can also be accompanied by musical instruments such as guitars. The results of the study show that the Incang-incang Tradition has been present in the community since 1980 because the community began to do incang-incang so that many people liked it, until in 2001 it began to be implemented in certain activities in the community. Over time, Incang-incang became increasingly well-known as evidenced by the large number of speakers at that time who could speak Incang-incang. However, Incang-incang did not get the proper form of recognition for the young people of Pedamaran society. So, nowadays there are only a few speakers of incang-incang and they are dominated by the elderly. From the results of this study, it is hoped that incang-incang can be pursued harder so that it can be enjoyed by the younger generation through several performances organized by the local government. Therefore, it is hoped that Incang-incang can become the pride of the Pedamaran community as an entertainment activity for the community itself.